Dietary inclusion of a lipase enzyme in the bioproductive indicators of laying pullets - Zúñiga, S. N.; Vaca, J. A.; Martínez, Y.; Rodríguez, R. (Cuban Journal of Agricultural Science, 2024)
A total of 700 one-day-old Dekalb White® birds were randomized into two treatments and seven repetitions to evaluate the inclusion of 0.01 % of a lipase enzyme with an energy contribution of 0.42 MJ/kg during five productive stages: starter 1 (1- 3 weeks) starter 2 (4-6 weeks), grower (7-10 weeks), development (11-15) and pre-lay (16-17). The inclusion of lipase decreased the cost of the diets by 12.21 USD/t in relation to the control treatment. During weeks 1-3, 7-10 and 16-17 no notable changes (P>0.05) were recorded for body weight, feed intake, feed conversion ratio and viability. However, in weeks 4-6, the inclusion of lipase improved (P<0.05) body weight (408.96 vs 449.36 g) and feed conversion ratio (2.32 vs 1.95). However, this treatment (lipase) increased (P<0.05) feed intake and feed conversion ratio in weeks 11-15 (3.24 vs 4.11). In the global period (1-17 weeks), no productive indicator of the pullets changed (P>0.05) due to the effect of the experimental diets. It is recommended to include the lipase enzyme (Lipase AN6) in hypocaloric diets (-0.42 MJ/kg) to reduce its cost, without affecting the bioproductive indicators of laying pullets.